2002
DOI: 10.1089/15270290260131911
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent Hypoxic Training: Fact and Fancy

Abstract: LTITUD E TRAINING has been used frequently by endurance athletes to enhance performance. However, not all athletes or teams have the resources to travel to high altitude environments on a regular basis. Moreover, issues such as availability of adequate training facilities have limited the use of mountain-based altitude training. In the last few years, there has been a remarkable increase in the number of techniques designed to "bring the mountain to the athlete." Nitrogen houses, hypoxia tents, and special bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
142
0
5

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 160 publications
(158 citation statements)
references
References 110 publications
5
142
0
5
Order By: Relevance
“…9,10 Interest in this topic was aroused because of the excellent results in endurance events (with predominant aerobic metabolism) achieved by African athletes residing at moderate altitudes. 11 It was the incursion of these athletes at the 1968 Mexico Olympics, and their subsequent overwhelming dominance in these events that spurred studies into finding explanations for these quantitative differences in physical performance.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Interest in this topic was aroused because of the excellent results in endurance events (with predominant aerobic metabolism) achieved by African athletes residing at moderate altitudes. 11 It was the incursion of these athletes at the 1968 Mexico Olympics, and their subsequent overwhelming dominance in these events that spurred studies into finding explanations for these quantitative differences in physical performance.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, scientific studies showed conflicting results probably due to the complex adaptation of training load in hypoxia (Levine, 2002). The 'living high-training low' (LHTL) model purposed by Levine et al (1991) reduces the deleterious effects of altitude exposure during training caused by reduced exercise intensity.…”
Section: Introductionmentioning
confidence: 99%
“…Erythropoietin (EPO) is largely produced by the cells of the kidney and is responsible for the regulation of red blood cell production (see review: Wang and Semenza, 1996). The drop in tissue partial pressure of O 2 (P O 2 ), resulting from both environmental hypoxia and altitude, has the ability to encourage EPO release (see reviews : Wilber, 2001;Levine, 2002). Despite the depth of research supporting hypoxic-induced increases in EPO, there is still evidence contradicting such findings (Table 1).…”
Section: Introduction Ementioning
confidence: 99%